2019
DOI: 10.1002/jia2.25389
|View full text |Cite
|
Sign up to set email alerts
|

Motives for choosing, switching and stopping daily or event‐driven pre‐exposure prophylaxis – a qualitative analysis

Abstract: Introduction In settings where both daily and event‐driven pre‐exposure prophylaxis (PrEP) are offered to men who have sex with men (MSM), a clear understanding of the motives to choose between the different dosing‐regimens can facilitate more effective PrEP implementation. We therefore studied the motives for choosing for, switching between, and stopping daily or event‐driven PrEP. Methods We used data (August 2015‐June 2017) from the prospective, longitudinal, open‐label Amsterdam PrEP demonstration study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 58 publications
(85 reference statements)
5
46
0
Order By: Relevance
“…In our sample, 49.1% of the former PrEP users indicated that a reduced need for PrEP was a reason for stopping it. This is in accordance with findings from other studies of former PrEP users, where about half of the participants indicated stopping PrEP due to a perceived lower HIV risk [ 33 35 ]. This has also been described as ‘seasons of risk’, which suggests that HIV risk can undergo periodic changes over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our sample, 49.1% of the former PrEP users indicated that a reduced need for PrEP was a reason for stopping it. This is in accordance with findings from other studies of former PrEP users, where about half of the participants indicated stopping PrEP due to a perceived lower HIV risk [ 33 35 ]. This has also been described as ‘seasons of risk’, which suggests that HIV risk can undergo periodic changes over time.…”
Section: Discussionsupporting
confidence: 92%
“…Other reasons for stopping PrEP identified modifiable barriers. Financial burden and lack of health insurance cover have been identified as reasons for stopping PrEP [ 33 35 ] and in our sample 26.1% of former participants indicated that PrEP had become unaffordable. Since September 2019, about 3 months after the data collection for this analysis stopped, the costs for PrEP were covered by statutory health insurance in Germany when prescribed by HIV specialists.…”
Section: Discussionmentioning
confidence: 81%
“…An individual's choice of regimen over time is also likely to fluctuate with changing sexual and social contexts [7] . To date, reasons for changing PrEP regimens can only be inferred from single studies assessing hypothetical preferences after initiating PrEP [8] or qualitative analysis [9] , while no long-term longitudinal study on this issue has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…All participants were mindful of adverse events and concerned about potential harm. Both this fear, and that of resistance to PrEP [ 39 ] were potential barriers to PrEP initiation [ 14 , 16 ], and needs to be addressed by professionals [ 40 ], or improved sexual health promotion through new interventions such as dating apps and social media [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%